The Relationship between Clinical Symptoms and Urine Culture in Adult Patients with Acute Epididymitis - Kim, Sung Dae; Kim, Sun Wook; Yoon, Byung Il; Ha, U-Syn; Kim, Sae Woong; Cho, Yong-Hyun; Sohn, Dong Wan (The world journal of men's health, 2013)
We evaluated adult patients with acute epididymitis to identify the frequency of actual sexual contacts and the causative organism, and compared clinical examinations, degrees of manifested symptoms, and radiological test results. We reviewed the medical records of 65 patients older than 18 years presenting with acute epididymitis who had been treated between 2002 and 2011. Scrotal ultrasonography, urinalysis, and urine culture were performed to diagnose the acute epididymitis. Patients were divided into negative (n=45) and positive (n=20) urine culture groups. Then the latter groups were subdivided into a sexually transmitted organism (STO) culture group (n=13) and a non-STO (n=7) culture group. Data on any history of sexual contact, scrotal pain and tenderness, symptoms of urethritis (discharge, dysuria, urethral burning, or irritation), and lower urinary tract symptoms (dysuria, frequency, and urgency of urination) were obtained from all of the subjects. Patients in the positive urine culture group were significantly younger than those in the other group (p=0.224) and were more likely to have a history of sexual contact at least two weeks prior to onset of epididymitis (p=0.012). They had also a significantly enlarged epididymal head and significantly more severe complaints of pain or tenderness than those of latter group (p=0.348, p=0.288). However, the difference in these measures between the STO and non-STO group was not significant, except in the case of age (p=0.044). Patients of the positive urine culture group with acute epididymitis were significantly younger and more sexually active than the others. They also had severe pain or tenderness and an enlarged epididymal head. There was a close association between clinical symptoms, a positive urine culture, and ultrasonographic findings.